1, 2‐dibromo‐4‐(1, 2 dibromoethyl) cyclohexane (TBECH)–mediated steroid hormone receptor activation and gene regulation in chicken LMH cells. (3rd March 2014) - Asnake, Solomon; Pradhan, Ajay; Banjop‐Kharlyngdoh, Joubert; Modig, Carina; Olsson, Per‐Erik
Abstract The incorporation of brominated flame retardants into industrial and household appliances has increased their occurrence in the environment, resulting in deleterious effects on wildlife. With the increasing restraints on available compounds, there has been a shift to using brominated flame retardants that has seen the production of alternative brominated flame retardants such as 1, 2‐dibromo‐4‐(1, 2 dibromoethyl) cyclohexane (TBECH), which has been detected in the environment. In previous in silico and in vitro studies the authors have shown that TBECH can activate both the human androgen receptor (hAR) and the zebrafish AR (zAR) suggesting that it is a potential endocrine disruptor. The present study was aimed at determining the interaction of TBECH with the chicken AR (cAR). In the present study, TBECH bound to cAR, but in vitro activation assay studies using the chicken LMH cell line showed it had a potency of only 15% compared with testosterone. Sequence difference between ARs from different species may contribute to the different responses to TBECH. Further quantitative reverse‐transcriptase polymerase chain reaction (qRT‐PCR) analysis showed that TBECH interacted with and altered the expression of both thyroid receptors and estrogen receptors. In addition, the qRT‐PCR analysis showed that TBECH altered the transcription pattern of genes involved in inflammatory, apoptotic, proliferative, DNA methylation, and drug‐metabolizing pathways. This demonstrates that TBECH, apart from activating cAR, can also influence multiple biological pathways in the chicken. Environ Toxicol Chem 2014;33:891–899. © 2013 SETAC